Co₂ separations and the role of surface functionality - Wadi, Basil (Cranfield University, 2021)
To curb irreversible environmental effects of climate change, urgent measures must be taken to limit anthropogenic emissions and achieve net-zero carbon goals by 2050. Carbon capture technology to meet these goals is wide ranging, with novel methods directed at biogas upgrading or direct air capture. Biogas is produced from the anaerobic digestion of biological waste and considered a valuable renewable energy source; to produce biomethane for use interchangeably with natural gas. However, widespread use of established separation processes is limited, primarily due to low CO₂ selectivity or high energy demands of cyclic operation. One method to tackle these issues is the development of novel sorbents for use in pressure swing adsorption, targeting maximum CO₂ capacity and selectivity, while minimising regeneration energy penalties. Adsorbents incorporated with amines can meet one of these criteria, selectively adsorbing CO₂, but require high regeneration energies. Herein, the adsorption performance of a diverse range of amines grafted on mesoporous silica at varying densities is studied, to understand developing adsorption mechanisms, and identify the ideal degree of functionalisation for gas separations. It was found that although high amine densities led to the highest enhancement in CO₂ capacity and selectivity, moderate levels have comparable selectivity and capacity in isothermal adsorption-desorption conditions, standing out are di- and secondary amines. Diamine loadings achieved an adsorption capacity of 1.12 mmol/g, a heat of adsorption of 35-50 kJ/mol, and an IAST selectivity of 374 at CO₂ partial pressures of 40 kPa. Secondary amines had a low capacity of 0.67 mmol/g, but a higher heat of adsorption comparatively. The optimal binder formulation for pellet preparation of amine grafted silicas was also studied, a necessary step in conducting laboratory scale fixed-bed adsorption studies. When applying amines for ambient air adsorption, very high amine loadings result in slow adsorption kinetics, rendering the advantage of their high capacity debatable. Moderate loadings of primary and triamine under humid conditions have higher adsorption rates >250 µg/g/min, making them more suited for fast cycle processes.
Manovic, Vasilije - Associate Supervisor
Keywords: Carbon capture; mesoporous silica; SBA-15; amine functionalisation; biogas upgrading; direct air capture; pellet formation